2012
DOI: 10.1128/aem.05663-11
|View full text |Cite
|
Sign up to set email alerts
|

Acinetobacter Insertion Sequence IS Aba11 Belongs to a Novel Family That Encodes Transposases with a Signature HHEK Motif

Abstract: Experimental and in silico PCR analysis targeting ISAba11 and TnAbaR islands in 196 epidemiologically unrelatedAcinetobacter strains representative of >19 species were performed. The first two Acinetobacter baumannii ISAba11 elements identified had been found to map to the same site on TnAbaR transposons. However, no further evidence of physical linkage between the two elements was demonstrated. Indeed, examination of 25 definite or putative insertion sites suggested limited sequence specificity. Importantly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…It was recently shown that the ISAba11 elements belong to a novel family that encodes transposases with a signature HHEK motif and had been found in many kinds of Acinetobacter spp. [36]. The ISAba11 in the pAP-D499 was associated with typical 5-bp DR and possessed 13-bp TIR as previously reported [36].…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…It was recently shown that the ISAba11 elements belong to a novel family that encodes transposases with a signature HHEK motif and had been found in many kinds of Acinetobacter spp. [36]. The ISAba11 in the pAP-D499 was associated with typical 5-bp DR and possessed 13-bp TIR as previously reported [36].…”
Section: Discussionsupporting
confidence: 72%
“…[36]. The ISAba11 in the pAP-D499 was associated with typical 5-bp DR and possessed 13-bp TIR as previously reported [36]. ISAba11 movement can result in inactivation of the A. baumannii lipid A biosynthesis genes lpxA and lpxC, resulting in the loss of lipopolysaccharide production and high-level colistin resistance.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…There are several clades within this family. A new clade, ISAba11, was proposed as a new family based on five IS (156). Members of this group generate 5 bp target duplications (instead of 4 bp), exhibit conserved IR and include HHEK instead of YREK.…”
Section: Is701mentioning
confidence: 99%